Feasibility Study for Expansion of Child Development Center - Fitch, Naomi; San Joaquin Delta Coll., Stockton, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This document contains recommendations and the rationale for expansion of existing child care development center facilities at San Joaquin Delta College. Such expansion, in addition to providing immediate child care to children of parents enrolled at the college, would provide vocational training and in-service training opportunities, and would provide a learning laboratory for classes both within the college and from other institutions. Alternative facilities, with an on-campus location preferred, are described. It is proposed that the facility charge for its services on a sliding scale basis. Additional funding could be anticipated from internal college sources and from external agencies. A projected itemized operating budget is included as is a list of other colleges with child care facilities. Summary information on organization, staffing, and operating budgets of child care centers at 11 other California community college campuses is attached. (Author/JDS)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Budgets; Child Development Centers; Community Colleges; Costs; Day Care Centers; Facilities; Facility Expansion; Feasibility Studies; Two Year Colleges; San Joaquin Delta College CA; Guides, General